Respuesta :
Answer:
[tex]y=-8x^2+48x-74[/tex]
Step-by-step explanation:
A parabola that has a vertex of (3, -2) a focus of (3, -2 1/16), then the line of symmetry is x = 3.
The distance between the vertex and focus is equal to p/2, so
[tex]\dfrac{p}{2}=\sqrt{(3-3)^2+\left(-2+2 \dfrac{1}{16}\right)^2}=\dfrac{1}{16},[/tex]
so parabola's equation in vertex form is
[tex](x-x_0)^2=-2p(y-y_0)\\ \\(x-3)^2=-2\cdot \dfrac{1}{16}\cdot (y+2)\\ \\(x-3)^2=-\dfrac{1}{8}(y+2)\\ \\8(x-3)^2=-(y+2)[/tex]
In standard form this equation is
[tex]8(x^2-6x+9)=-y-2\\ \\y=-8x^2+48x-72-2\\ \\y=-8x^2+48x-74[/tex]
Answer:
y = –x2 + 6x – 11
Step-by-step explanation:
plz give brailyest and this one is the actual answer